2007
DOI: 10.5694/j.1326-5377.2007.tb01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital costs of older people in New South Wales in the last year of life

Abstract: Objective: To estimate hospital inpatient costs by age, time to death and cause of death among older people in the last year of life. Design and setting: Cross‐sectional analytical study of deaths and hospitalisations in New South Wales from linked population databases. Participants: 70 384 people aged 65 years and over who died in 2002 and 2003. Main outcome measures: Hospital costs in the year before death. Results: Care of people aged 65 years and over in their last year of life accounted for 8.9% of all ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 15 publications
7
57
0
1
Order By: Relevance
“…In line with this, several studies have found a lower rate of health care utilisation and transitions for the oldest old at the end-of-life compared to younger decedents due to the higher proportion of nursing home residents in the highest age group [8,9]. In Switzerland, data on age differences in the end-of-life treatment are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, several studies have found a lower rate of health care utilisation and transitions for the oldest old at the end-of-life compared to younger decedents due to the higher proportion of nursing home residents in the highest age group [8,9]. In Switzerland, data on age differences in the end-of-life treatment are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Our data should also be considered lower than that reported by other authors in Italy (75% of deceased with at least one hospitalization in the last year of life; 42.1% of patients died in hospital) and in other countries as well as Sweden (42.1% of all deaths occurred in hospitals), Portugal (54.5% of all deaths in hospital) and Canada (73.4% died in hospital) 13–16 . Moreover, a further study carried out in the New South Wales in 2002 found that people aged 65 years and over who were in their last year of life used an estimated 10.3% of all hospital days and 8.9% of total hospital inpatient costs, of which more than 40% was spent in the last month of life 17 . One explanation for the reduced hospitalization of patients in our area in the last part of life could be, at least in part, attributed to the role played by PC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, average costs associated with hospital inpatient care are known to increase exponentially in the past 3 months of life 9. Certain groups have been identified as being more likely to experience a hospital admission in the last year of life.…”
Section: Introductionmentioning
confidence: 99%